Acid modified H-USY zeolite for efficient catalytic transformation of fructose to 5-hydroxymethyl furfural (biofuel precursor) in methyl isobutyl ketone-water biphasic system - Pande, Ashwini; Niphadkar, Prashant; Pandare, Kiran; Bokade, Vijay (Energy Fuels, 2018)
Sustainable process and efficient heterogeneous acid catalyst for the preparation of platform chemicals like 5-hydroxymethyl furfural (5-HMF) from renewable source is much in demand in the context of heterogeneous catalysis. Commercially available solid acid catalyst, H-USY zeolite was modified by treating with aqueous solution of H3PO4 and H2SO4 (10–30 wt %). Modified H-USY was completely characterized by XRD, NH3-TPD, energy dispersive analysis X-ray (EDAX), FT-IR, pyridine-IR, and NMR. Its catalytic performance was evaluated for the fructose conversion to 5-HMF in methyl isobutyl ketone (MIBK)–water system. Modified H-USY zeolite was identified to have potential in enhancement of 5-HMF yield up to 65% from 32% (parent H-USY) with minimum formation of furfural (8%). H-USY modified with 10 wt % H3PO4 (10P–Y) was found to be the best compared to other studied catalysts, namely, H-USY modified with 20 and 30 wt % H3PO4 (20 and 30P–Y) or 10–30 wt % H2SO4 (10- to 30S–Y). Best performance of 10P–Y is associated with the optimum combination of moderate acidity (both weak as well as strong), moderate dealumination of Al from extra-framework sites as well as from framework sites of H-USY, formation of new Al–O–P bonds between framework Al and elemental monomeric phosphorus, presence of Brønsted as well as Lewis acidity, and creation of mesopores. This gives new insight on a potential heterogeneous acid catalyst for the synthesis of 5-HMF.

Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment